Blaženje sindroma sproščanja citokinov pri covid-19 - Jakopin, Žiga (Farmacevtski vestnik, 2020)
Severe coronavirus disease 19 (covid-19) is characterized by a surge of pro-inflammatory cytokines, termed cytokine storm. As the SARS-CoV-2 virus evades early clearance by the immune system, high viral load, and endothelial and pulmonary epithelial cell apoptosis in later stages of infection are responsible for infiltration of lung tissue by neutrophils and macrophages. These, in turn, release cytokines, attracting further immune cells to the site of inflammation. High concentration of cytokines induces leakage of blood vessels, acute respiratory distress due to alveolar edema, activation of coagulation pathways, and consequent irreversible damage to lungs and other organs. Blocking the release or interfering with pro-inflammatory cytokine signalling should thus be considered as supportive therapy for severe covid-19. Here, we review therapeutic strategies aimed at alleviating covid-19-related cytokine storm. Some of the most promising immunomodulatory drugs being evaluated for this indication in on-going clinical trials are Janus kinase inhibitors, interleukin 6 and 1 antagonists, azithromycin and hydroxychloroquine.
Keywords: Citokini; citokinska nevihta; imunomodulatorji; pandemija covid-19; Pandemije; SARS-CoV-2; sindrom sproščanja citokinov